Construction and study of local linearization adaptive codes for ordinary differential equations - Sotolongo Aguiar, Alina (2014)
The aim of this work is to construct adaptive integrators for ordinary differential equations based on the Local Linearization method. Different orders of the involved Padé approximation are considered and their effect on the adaptive integrators is studied.